PENGARUH LINGKUNGAN KERJA, FASILITAS KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. READS MEDIA INDONESIA - Mustapa, Zainuddin (Siddiq Institute, 2024)
This research aims to examine, analyze and interpret the influence of the Work Environment, Work Facilities and Job Satisfaction on the performance of PT employees. Reads Media Indonesia. This research is descriptive quantitative, the population and sample are 32 employees. Data collection methods use interviews, questionnaires and literature studies. The research data will be analyzed using statistical testing tools using SPSS 24 software. The research results show that: 1. The work environment has a positive and significant effect on the performance of PT employees. Reads Media Indonesia. In general, the work environment has a strong influence on improving employee performance. Employee performance is very important for achieving the goals of an organization 2. Work facilities have a positive and significant effect on the performance of PT employees. Reads Media Indonesia. Work Facilities are a factor that really supports all employee activities with full awareness in developing their energy and thoughts to the maximum to support organizational goals. 3. Job satisfaction has a positive and significant effect on the performance of PT employees. Reads Media Indonesia. The purpose of Job Satisfaction is to fulfill the economic needs of Employees, and to increase work productivity in advancing the organization or organization because Employees have the motivation to work better to obtain the training that has been determined.